Mountains too high and valleys too deep drive population structuring and demographics in a Qinghai–Tibetan Plateau frog Nanorana pleskei (Dicroglossidae). Issue 1 (18th December 2016) - Zhou, Weiwei; Jin, Jieqiong; Wu, Jun; Chen, Hongman; Yang, Junxiao; Murphy, Robert W.; Che, Jing
Abstract: Pleistocene glacial–interglacial climatic oscillations greatly shaped the current genetic structure of many species. However, geographic features may influence the impact of climatic cycling. Distinct geographic and environmental characters between northern and southern parts of the eastern Qinghai–Tibetan Plateau (EQTP) facilitate explorations into the impacts of geographic features on species. The northern parts of EQTP contain large areas of marsh, and the environment is rather homogeneous. In contrast, the southern EQTP harbors complex alpine valleys and a much more heterogeneous setting. We evaluate DNA sequence variation from both the mitochondrial and nuclear genomes in Nanorana pleskei, a species endemic to the EQTP. Hypothesis testing on the evolutionary history of N. pleskei indicates that northern populations can disperse freely, but alpine valleys isolate southern populations. Demographic histories between northern and southern populations also differ. Northern populations appear to have experienced population expansions, while southern frogs exhibit a far more stable demographic history. By combining climatic analyses and species' distribution models, our study suggests that geographic and environmental features drive the differences between the northern and southern EQTP. Abstract : In east edge of Qinghai–Tibetan Plateau, geographic features are quite different between northern and southern parts. Using Nanorana pleskei (Amphibia: Anura: Dicroglossidae) as model species, we explored how these differences impact evolutionary history of organisms in this region.